Eudemian Ethics on what is “true but not clarifying” - Zillig, Raphael (Revista Archai, 2017)
In Eudemian Ethics I 6, Aristotle describes the progress of the ethical investigation as a drift from a) what is true but not clarifying to b) what is true and clarifying. The drift from a) to b) is usually interpreted as the overcome of a first obscure and confused grasp of the subject by a more accurate and reliable account. In this paper, I claim that the understanding of the methodological role of a) depends upon it’s dissociation from the notions of obscurity and confusion. What is true but not clarifying should be rather understood as a first indistinct (but not confused) grasp of the subject. It’s insufficiency as regards explanation is to be accounted on the base of its indistinctness and not on it’s supposed obscurity.